Yuqaṭṭil, Yaqaṭṭil, or Yiqaṭṭil: D-Stem Prefix-Vowels and a Constraint on Reduction in Hebrew and Aramaic - Steiner, Richard С.
ersch. 1981; Babylonian tradition and ancient transcriptions suggest Yiqaṭṭil.